Chapter Gli apporti della geografia alla definizione operativa dell'eco-territorialismo. Tra storie disciplinari e geografie indisciplinate del cibo - Dematteis, Giuseppe (Territori, 2023)
Partly due to its composite nature, geography has since long given important contributions to the multidisciplinarity of the territorialist approach. This chapter intends to continue and deepen such hybridisation of knowledge and reflection areas with reference to the evolutionary tendencies underway, both in geography and in territorialist theory and practice, in view of the transformations of the food system and the renewed public and scientific attention to food/territory relationship: a theme, intrinsically rebellious to disciplinary fences, which opens up the field of planning to a broad and multifaceted reading of the ecological relations structuring human settlements.